Influence Coefficients of Constructive Parameters of Meander Slow-Wave System with Additional Shields - Metlevskis, Edvardas; Martavičius, Romanas; Katkevičius, Andrius; Plonis, Darius (Electrical, Control and Communication Engineering, 2016)
Constructions of meander slow-wave systems with additional shields grounded at different positions are presented. The construction of meander slow-wave systems with additional shields grounded at both edges is investigated in detail. The influence of the main constructive parameters on the electrical characteristics of meander slow-wave systems with additional shields grounded at both edges is evaluated. The main constructive parameters of the investigated system are: the length of the conductor, the width of meander conductor, the width of additional shield, and the width of the gap between adjacent meander conductors.